Placement of permanent pacemaker in a low-birth-weight infant with congenital heart block: a case report - Naela Ashraf,; Fatima, Rabika; Atiq, Mehnaz; Amanullah, Muneer (Journal of the Pakistan Medical Association, 2023)
One of the rare diseases with a high mortality rate in infants is congenital heart block (CHB) with neonatal lupus erythematosus (NLE) as the most common cause. A permanent pacemaker (PPM) is indicated for symptomatic bradycardia. The choice of PPM in the paediatric population is different from that in the adult population because of several reasons like small size, account of somatic growth, and difference in physiological changes. Here, we present a case in which a 2.6 kg and 45 days old baby with CHB secondary to NLE was successfully treated with a single-chambered adult-sized PPM with epicardial lead. According to our knowledge, this is the smallest baby in Pakistan in which PPM has been implanted. Keywords: Neonatal lupus erythematous, infant low birth weight, cardiac pacemaker, permanent pacemaker implantation (ppm), congenital complete heart block.